IMPROVING ACCOUNTING LEARNING ACHIEVEMENT BY APPLYING THE COOPERATIVE LEARNING MODEL IN CLASS X ACCOUNTING STUDENTS OF STATE VOCATIONAL SCHOOL 4 PADANGSIDIMPUAN FOR THE 2019/2020 ACADEMIC YEAR - Caniago, Aisyah (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
In small group teaching, it is possible for the teacher to pay attention to each student and the occurrence of a closer relationship between teacher and student as well as between students and students. Sometimes students find it easier to dance and teach their own friends. In this case small group teaching can meet these needs. This teaching allows students to learn creative and leadership traits in students, and can meet student needs optimallyThis research is based on the problem of (a) how to improve learning achievement in accounting subjects with the application of cooperative learning mode? (b) How is the effect of the cooperative learning model in increasing interest, attention and participation in learning accounting subjects?While the objectives of this research are (a) To know the improvement of student achievement after the implementation of cooperative learning model, (b) to know the effect of student learning motivation after the implementation of cooperative learning model, (c) to improve the implementation of Accounting subject learning in improving student achievement.This study uses three rounds of action research. Each round consists of four stages, namely: planning, activities and observations, reflection and revision. The targets of this study were students of class X accounting at SMK Negeri Padangsidimpuan for the academic year 2019/2020, the data obtained in the form of formative test results, observation sheets for teaching and learning activities.From the results of the analysis, it was found that student learning achievement has increased from cycle I to cycle III, namely, Cycle I (68%), cycle II (76%), cycle III (88%)The conclusion of this study is the TAPPS cooperative learning method can have a positive effect on achievement and learning motivation of class X Accounting students at SMK Negeri Padangsidimpuan and this learning model can be used as an alternative to learning accounting subjects. More about this source textSource text required for additional translation information